Application of Boarding House Rental Location Search System Based on Android - Muhammad Akram Hamzah; Nur Mustika; Mahmud Mustapa; Ummiati Rahmah (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
Boarding houses have become a fairly important need for many people, especially for students studying outside the area who choose boarding houses as temporary housing, and students whose homes may be quite far from the campus, who rent boarding houses near their campus so as not to spend a lot of energy and time traveling. The boarding house route search information system has benefits for users who will search for the nearest boarding house from various features, such as finding boarding house routes and viewing detailed boarding house information. ease of boarding house owners to manage data allows information to be continuously updated. This study aims to create an Android-based boarding house location information system. The research stage starts from the design of a system that has been built using a Use Case Diagram that has three actors, including the admin, the boarding house owner, and the tenant/user. Each of these actors has different roles and access rights. At the implementation stage of the system creation process, using the Android Studio application, the system is tested using the Black Box method. Based on the results of system tests that have been carried out, obtaining good results, or in other words, the system can run as expected.